(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The present study deals with gypsiferous soils in selected areas in middle of Iraq, the field study includes ten sits chosen according to their abundant of gypsum, one site in Al Diwaniya governorate, one site in Al Najaf governorate five sites in Al Najaf-Karbala area and three sites in Karbala governorate. Petrographic study and grains size analysis were used to identify the texture, type of minerals and their forms. Scanning electronic microscope technique was also used for illustrating habits of gypsum within soils. X-ray diffraction was used to classify minerals that occur while using the technique of X-ray fluorescence to determine the chemical composition of major oxides. The percentage of gypsum in the studied sits was compared with several classifications to determine its suitability for irrigated agriculture and crops